Efektivitas Pembelajaran Berbasis Online Dengan Google Classroom Terhadap Hasil Belajar Siswa Kelas V Mata Pelajaran Pendidikan Agama Buddha dan Budi Pekerti di SD W.R. Supratman 1 Medan Tahun Ajaran 2020/2021 - Limurty, Chintya; Lamirin, Lamirin; Nuriani, Nuriani; Winata, Surya Hadi (Jurnal Ilmu Agama dan Pendidikan Agama Buddha, 2021)
the nation in reducing the spread of COVID-19 pandemic. Learning is then no longer dependent on textbooks for many, and now both educators and students know to utilize e-learning technology as a tool for study. Educational activities online use many different methods and features, a number of which involve programs like Zoom Meeting, Google Classroom, Google Meet, Schoology, Learning Management system (LMS) and more. This systemic transition in education during the pandemic, with the pertinent technology, is hoped to achieve maximization in academic competency. This change is also hoped to be able to spur motivation in students and yield better academic results among the Primary Level 5 students in the Buddhist and Moral Education class with the application of Google Classroom at SD W.R. Supratman 1 Medan. The effectiveness of learning as a measure of the success of a learning process between students and students, or students with teachers in achieving learning goals and changes to this online or online-based learning system form learning that makes students independent and not dependent on others and students are able to pursue competence in learning by using the Google Classroom application at SD W.R. Supratman 1 Medan. This study uses the quantitative method of data sampling and compiling with questionnaires filled by the research subjects (5th Grade Students of W.R. Supratman 1) for whole total sampling in one semester. Resultant data reveal that R2 (R Squared) is valued at 0.031. This shows that in percentages the independent variable (online study effectiveness using Google Classroom) juxtaposed against the dependent variable (academic results from Elementary Level 5 students on Buddhism and Morals) stand at 3.1%, leaving the rest of 96.9% nailed to miscellaneous variables. The use of Google Classroom has a positive impact on learning outcomes for Buddhist and Moral Education subjects, so all those involved can improve learning facilities so as to create comfortable and comfortable learning conditions effective for teachers and students.